SENSITIVITY SOLUTION OF KERSEN LEAVES (Muntingia calabura L.) AGAINST BACTERIAAeromonas - Wijaya, Rahmat Santosa; Lukistyowati, Iesje; Syawal, Henni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Disease that often develops in aquaculture is one of them is red spot disease.This disease is often called Motile Aeromonas Septicemia (MAS) caused byAeromonas hydrophila.Natural ingredients that can be used as prevention and treatment of fish diseases are kersen leaf plant (Muntingia calabura L) which is antibacterial and antimicrobial.This research was conducted in December 2018-February 2019 in the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine, University of Riau. The purpose of study was to determine the sensitivity of solution of kersen leaves to inhibit the growth of bacteria Aeromonas hydrophila and to know LD50solution of kersen leaves to jambal siam (Pangasius hypophthalmus) by immersion. Research method used is the experimental method, for sensitivity testusing the method of Kirby Bauerdisc with dosage used were 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, 9%, 8%, 7%, 6%, 5% , 4% and controls (Oxytetracyclin). The results showed that the solution of kersen leaves can inhibit the growth of bacteriaA. hydrophila starting from a dose of 100% -4% with an average diameter of inhibition zones ranging from 13.55 - 6.25 mm. LD50 test of the solution of kersen leaf (M. calabura L.) againstjambal siam (P. hypophthalmus) by immersion for 24hoursis at a dose of 3.6%. Keywords: M. calabura L., Motil Aeromonas Septicemia, Kirby Bauer discs, LD50